Fire resistance of steel and composite columns - Phng, Eugene Guan Hwee (2008)
A programme of experimental testing has been conducted to investigate the behaviour of steel columns and concrete-encased steel section composite columns at elevated temperature. Heating is attained in an electric furnace. Measurements of internal forces, lateral deflections, axial displacements and temperatures are reported. Twenty steel column specimens were subjected to elevated temperatures. One loading test was carried out at ambient temperature to determine the working load to be applied to the other specimens in the same series for elevated temperature tests. The variable parameters were slenderness ratio and axial restraint ratio. The experimental measurements are presented and compared with predictions from numerical simulations using FEMFAN-3D, a program developed by NTU. It is concluded that buckling temperature decreases as slenderness ratio increases, under a fixed restraint ratio. Applying increased axial restraint to the columns has a negative effect of reducing the buckling temperatures.